Velocity map imaging as a tool for gaining mechanistic insight from closed-loop control studies of molecular fragmentation - Jochim, Bethany; Averin, R.; Gregerson, Neal; McKenna, J.; De, S.; Ray, D.; Zohrabi, M.; Bergues, B.; Carnes, K. D.; Kling, M. F.; Ben-Itzhak, I.; Wells, E. (My University, 2011)
Strong-field closed-loop control schemes using shaped ultrafast laser pulses have been used to selectively fragment a variety of molecules in recent years. The resulting pulses are often complex and resist an easy mechanistic interpretation. We report on the use of velocity map imaging to study the dissociative ionization of CO molecules by optimally-shaped ultrafast laser pulses. Using this technique, a mechanism is identified for the optimized CO+ → C + O+ dissociation, and some of the observed control over the CO+ dissociation branching ratio is ascribed to an angular discrimination effect. Furthermore, we demonstrate that the acquisition of two-dimensional velocity map images is rapid enough to incorporate directly into the adaptive control loop.